Hazard evaluation of air pollution by using the key characteristics approach. Issue 1 (April 2020) - Sone, Hideko; Ito, Tomohiro; Win-Shwe, Tin-Tin; Miki, Masahiro; Fujitani, Yuji; Nakajima, Daisuke
Abstract: The key characteristic (KC) as a new approach based on mechanistic evidence has been shown by the IARC Monographs Program working group. Human carcinogens like exhibit one or more key characteristics that are related to how they cause cancer, and different carcinogenic agents exhibit different spectra of these key characteristics. Air pollution is one of the major concerns of human health for the people who lives in Asia because air pollution contains many different human carcinogens including heavy metals, volatile compounds. electrophile compounds and polyaromatic hydrocarbon compounds. In this study, we investigated air pollution mixtures derived from diesel and gasoline engine exhausts by a mechanism-based approach. We first conducted a KC analysis of organic compounds of diesel exhaust in IARC monograph 105 using data of biological test results from the PubChem database. As a result, it was found that some PAH among those compounds is highly responsive to aryl hydrocarbon receptor, nuclear factor erythroid 2 like 2, NR1I2/3 nuclear receptor subfamily 1 group I member 2/3. Further, we analyzed KCs of water-extract mixtures from diesel exhaust particle (DEP-WM) using gene expression values in the mouse lung responded induced by exposures to DEP-WM. The KC of DEP-WM showed lipid related-nuclear receptor signaling and apoptotic pathway, suggesting that DEP-WM affects lipid metabolism in lung tissues. Thus, the KC method will be useful for high-precision assessment of a mixture of air pollution.